URBACH-WIETHE DISEASE: EXPERIENCE AT A TERTIARY CARE HOSPITAL IN ABBOTTABAD, PAKISTAN - Javeria, Javeria; ullah, Sami; Marium, Marium; far, Neelo; Samad, Fatima; Nabi, Ghulam; Ghazal, Saadia (Journal of Ayub Medical College Abbottabad, 2008)
Background: Urbache-Wiethe disease (Lipoid Proteinosis) is a rare autosomal recessive disorder characterized by the deposition of an eosinophilic hyaline-like material in the skin, larynx, mucous membranes, brain, and other internal organs. Methods: A survey of one year duration was carried out prospectively at the Department of Dermatology, Ayub Teaching Hospital Abbottabad to document cases of lipoid proteinosis. Cases were selected from the outpatients department on the basis of clinical presentation and were subjected to detailed examination and investigations after admission. Results: Five cases were diagnosed as suffering from Lipoid Proteinosis over the study period. All had typical features of hoarseness, skin lesions and tongue involvement. All were born of consanguineous parents. Three (60.0%) cases also gave a history of involvement of other family members, particularly cousins. Conclusion: This rare disease occurs in Hazara Division of North West Frontier Province of Pakistan with an as yet undetermined frequency and clinical suspicion is warranted to diagnose cases with the typical presentation. Key Words: Lipoid proteinosis, Urbach-Wiethe disease, Hyalinosis cutis et mucosae, Hoarseness